A pragmatic approach to imaging in large vessel vasculitis. (July 2015) - Patil, Pravin; Dejaco, Christian; Dasgupta, Bhaskar
<x xml:space="preserve">Abstract</x> Introduction: As the presentation of large vessel vasculitis (LVV) is manifold, diagnosing it before development of complications remains challenging. It is vital to reach an early diagnosis in order to prevent stenosis, aneurysms or occlusions. Imaging techniques can be helpful and in recent years the role of temporal artery ultrasound and the combination of positron emission tomography with computed tomography (PET-CT) have been highlighted. Areas covered: This article describes indications for imaging in LVV and discusses usefulness of available imaging modalities. Expert opinion: Ultrasonography and PET-CT play a very important role in the early diagnosis of LVV. Wherever possible, patients should receive the lowest possible immunosuppressive and GC therapy (< prednisolone 7.5 mg daily or equivalent) a week prior to the PET-CT. Because of its expense and significant radiation exposure, PET-CT is best selected for patients where other available investigations have been non-contributory. Vascular sonography can also be used during follow-up. There is an urgent need for classification of LVV based on imaging.